DESIGN AND IMPLEMENTATION OF ACCOUNTING AND FINANCIAL REPORTING SYSTEM AT PT. MUSTIKA INDO KEPRI - Ivone Ivone; Meiga Putri Antoni Ang (ConCEPt - Conference on Community Engagement Project, 2022)
Business in Batam, especially Micro, Small, and Medium Enterprises (MSMEs) often ignore the accounting recording system. Even though they using the system, the system is not applicable in accordance with the Financial Accounting Standard of Micro Small and Medium Entity (SAK-EMKM). By not following the system, many MSMEs do not know exactly the state of the company and only attach to the company’s profit. The company is also will be difficult to make decisions because there are no clear and correct financial statements. As one of the MSMEs in Batam, PT. Mustika Indo Kepri has been running for approximately 10 years, but the managed of accounting system is still done manually. Such recording is less efficient, causing financial reporting to provide less accurate information. Inaccurate reporting can make it difficult to find previous transactions and can also lead to frequent differences between record keeping and physical inventory. The data collection techniques are used start from the process of interviewing, observation and documentation with business owners in the period from September to December 2021. Systems designed using Microsoft Access are able to manage reports such as transaction of cash equivalents, purchase and sales transactions, general journal entry, journal recording adjustment, closing journal entry and inventory recording. So that the processed report will produce a statement of financial position, income statement, statement of change in equity, cash flow statement, and inventory statement